Epigenetics and reproductive health - Balasinor, Nafisa; Parte, Priyanka; Singh, Dipty (Translational epigenetics series, 2021)
Of the epigenome reprogramming of embryonic germ cell development -- Oocytes form a unique epigenome during oogenesis -- De novo DNA methylation and genomic imprinting during oogenesis -- Interplay between histone modification and de novo DNA methylation -- Broad domains of H3K4me3 during oogenesis -- Histone replacement during oogenesis -- Three-dimensional organization during oogenesis -- Epigenome reprogramming during the development of human germ cells -- PGC specification and migration in human embryos -- Reconstitution of early human PGCs and epigenome reprogramming in vitro.